Central line-associated bloodstream infection (CLABSI) with three different vascular access in neonatal intensive care unit - Dina Rabie; Mohammed F. Mostafa; Rania M. Abdel Halim; Ola Ahmad Ezzat (SpringerOpen, 2022)
Abstract Background Central venous catheters (CVCs) are a mandatory aspect in the neonatal intensive care units. Unfortunately, bloodstream infection is a frequent complication of CVCs. A needleless connector is attached to the end of CVC to allow infusion of fluids. We aimed to assess the effect of needleless connectors on central line-associated blood stream infection, and to assess rate of occurrence of bloodstream infection with the use of three different types of venous access in neonates. Methods This study is a prospective, randomized, comparative study which was held at the Neonatal Intensive Care, Faculty of Medicine, Ain Shams University. The study recruited 120 neonates who were categorized into three groups according to the type of inserted CVC: group A with umbilical venous catheter, group B with peripherally inserted central catheter, and group C with non-tunneled central venous catheter, and each group was further subdivided into two groups according to the use of needleless connector. Criteria of central line-associated bloodstream infection (CLABSI) and central line-related bloodstream infection (CLRBSI) were applied. Results The study included 120 neonates, a multivariable logistic regression analysis was held for two predictors (type of CVC and use of needleless connector) of CLABSI/CLRBSI, it revealed that the use of needleless connector was associated with significant lower incidence of CLABSI/CLRBSI (P value < 0.05, adjusted odds ratio [aOR] = 0.303), the use of peripheral inserted central catheter (PICC) was also associated with the lowest incidence of CLABSI/CLRBSI (P value = 0.015, aOR = 0.284). Another multivariable logistic regression analysis was done for four predictors (type of CVC, use of needleless connector, gestational age, and catheter dwell time) which revealed that the gestational age (P value = 0.001, aOR = 0.691) and catheter dwell time (P value = 0.004, aOR = 1.313) were the only independent predictors for the occurrence of CLABSI/CLRBSI. Conclusion The use of needleless connector can lower the incidence of CLABSI/CLRBSI, PICC line was associated with the lowest incidence of CLABSI/CLRBSI among the three types of CVCs. Low gestational age and long catheter dwell time were found to be the main risk factors for increasing the incidence of CLABSI/CLRBSI.